Assessing the sense of initiative and entrepreneurship in vocational students using the European qualification framework. Issue 7 (8th August 2016) - Morselli, Daniele; Ajello, Annamaria
Abstract : Purpose: – The purpose of this paper is to find a framework for the assessment of the learning outcomes of entrepreneurship education as a cross-curricular subject. The problem is twofold: the first difficulty is the relationship to the general issues regarding competence and its assessment; the second difficulty is the assessment of competencies in cross-curricular education in diverse contexts such as school and work. Design/methodology/approach: – The European key competence for lifelong learning of the sense of initiative and entrepreneurship and the European qualification framework (EQF) are convenient to benchmark the outcomes of enterprise education. In order to assess and develop competence in vocational students, educators should design real life problem solving situations, which are new for the students and closely related to their vocations. Findings: – The study describes an assessment process of the learning outcomes in terms of knowledge, skills and competence. While the authors tested knowledge by giving the students open-ended questions, the authors assessed the skills and competence with a practical problem concerning the students' vocational discipline to be solved in groups. Research limitations/implications: – The paper calls for a better alignment between work experience, teaching for competence and assessment of key competences – such as the sense of initiative and entrepreneurship – taught as a cross curricular subject. Originality/value: – The assessment makes use of a theoretically grounded definition of competence, and considers varied forms of evaluation of entrepreneurship education. Educators can use it across Europe as it refers to a common background, the European key competences and the EQF, and it promotes the students' transitions to work and mobility. It is rigorous, and, at the same time, adaptable to the context. It is meaningful for the various stakeholders at various levels: students, employers, schools, workplaces and institutions.